ISM-FLUX: MINFLUX with an array detector - Eli Slenders; Giuseppe Vicidomini (Physical Review Research, 2023)
Single-molecule localization based on the concept of MINFLUX allows for molecular resolution imaging and tracking with a laser-scanning microscopy architecture. In MINFLUX, a doughnut-shaped structured illumination beam sequentially excites the sample, thereby minimizing the localization uncertainty for a given number of photons. However, MINFLUX has a limited field of view (FOV) and therefore requires a precise prelocalization step. We mitigate this problem by introducing the single-molecule image scanning microscopy (smISM) concept. In smISM, the point detector of the laser-scanning microscope is replaced with a small single-photon detector array, thereby leveraging the benefits of both structured illumination and structured detection. We show via simulations that by combining smISM and MINFLUX (i.e., ISM-FLUX), we obtained a localization uncertainty between 1 and 15 nm over a FOV of more than 800 nm with 100 photons. In addition, smISM allows the localization of multiple molecules simultaneously. We calculate the effect of different parameters, such as the relative position of the doughnut beams, the number of detector pixels, the number of photons, and the signal-to-background ratio, on the localization uncertainty. We predict that the combination of a good localization precision and the enhanced robustness of ISM-FLUX will help the wide adoption of MINFLUX.